Expert System Diagnosing Damage to Canon Ir5000 Copier With Forward Chaining Method - mega indriani (Yayasan Kita Menulis, 2022)
A photocopy machine is a machine that works mechanically to fulfill the function of copying one document on a machine into another paper in black-and-white copies. During the copying process, various defects often occur, so a technician is needed to repair it. While waiting for the arrival of a technician to repair a damaged machine, it takes some time. Therefore, we need a strategy that can quickly find out the type of photocopier damage and how to handle it to help repair the damage to the photocopier. with the transfer of expertise by experts to be transferred again to other people who are not yet experts is the main goal of the system. In the process of drawing conclusions the system uses the Forward Chaining algorithm where the system will display symptoms of photocopy machine damage to be selected by the user, which can finally determine the solution to the damage to the machine. The results obtained from making this application are easier to obtain by making an expert system to diagnose photocopier damage and can be used and studied easily by the general public. for handling the problem of damage to the Canon IR 5000 photocopier using the Sublime Text Application as supporting software in terms of designing the layout of the application design, using the MySQL Database as a database design place and XAMPP v3.2.1 to run the database server and php.